Endoscopic hydro pneumatic dilatation as a therapeutic procedure in subglottic stenosis Servicio Desconcentrado Hospital Universitario de Pediatría Dr. Agustín Zubillaga (Boletin Médico de Postgrado, 2022)
Subglottic stenosis represents the most prevalent respiratory tract condition in pediatric patients with a history of prolonged orotracheal intubation. An ex post facto investigation was carried out, with retrospective data collection, with the aim to evaluate the results obtained with hydro pneumatic dilatation as a therapeutic procedure in patients with subglottic stenosis who attended the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga during the January 2016-March 2019 period. The sample included 13 patients (8 males and 5 females) aged between 2 to 12 years with prolonged intubation being the main cause of subglottic stenosis. The initial clinical manifestation of stenosis began to occur one month post intubation. The severity of airway occlusion was determined by the Myer and Cotton scale; the number of dilations varied between 4 and 7. No complications were reported after the procedure. In conclusion, endoscopic balloon hydro pneumatic dilatation is a highly effective minimally invasive procedure for the long term management of acquired subglottic stenosis in pediatric patients.
Keywords: laringostenosis; intubation; intratracheal, dilatation; pediatric, hospitals; therapeutics